Spatial and temporal variations of urban litter in Mar del Plata, the major coastal city of Argentina - Seco Pon, Juan Pablo (2012)
Urban littering is considered an important environmental and public issue globally. This problem isgrowing considerably within coastal communities of the southern region of South America. The goals of this study were to assess (1) the abundance and composition of urban litter; (2) the spatial and temporal variations of its abundance; and (3) the relationship between the abundance of litter and three anthropogenic variables (i.e. abundance of pedestrians, of parked vehicles, and of trash bins) in Mar del Plata, the most populated coastal city in Argentina. Eighty-eight transects, each covering 1425 m2, were sampled along four sites from April 2008 to March 2009. Results showed 20,336 items (ca. 14 items per m2) of which cigarette butts (33%), papers (31%), and plastics (22%) were the most commonly littered items. Higher amounts of litter were found in an industrial area (city´s harbor), while the abundance of litter appeared relatively even throughout the year. Redundancy analysis techniques indicated a high abundance of all three anthropogenic variables associated with the central business district area of the city and an area in close proximity to a major seaside resort, where cigarette butts and papers dominated. This is the ﬁrst study that has examined spatial and temporal variations of urban litter in a high-density coastal city in Argentina. Our results showed that addressing the problems associated with urban littermust include intensive educational and advertising campaigns directed at pedestrians and owners ofcoastal city in Argentina. Our results showed that addressing the problems associated with urban litter must include intensive educational and advertising campaigns directed at pedestrians and owner of parked vehicles, but waste reduction clean-up operations and law enforcement should be also considered.